Subnational variations in the quality of household survey data in sub-Saharan Africa - Valentin Seidler; Edson C. Utazi; Amelia B. Finaret; Sebastian Luckeneder; Gregor Zens; Maksym Bodarenko; Abigail W. Smith; Sarah E. K. Bradley; Andrew J. Tatem; Patrick Webb (Nature Communications)
Abstract Nationally representative household surveys collect geocoded data that are vital to tackling health and other development challenges in sub-Saharan Africa. Scholars and practitioners generally assume uniform data quality but subnational variation of errors in household data has never been investigated at high spatial resolution. Here, we explore within-country variation in the quality of most recent household surveys for 35 African countries at 5 × 5 km resolution and district levels. Findings show a striking heterogeneity in the subnational distribution of sampling and measurement errors. Data quality degrades with greater distance from settlements, and missing data as well as imprecision of estimates add to quality problems that can result in vulnerable remote populations receiving less than optimal services and needed resources. Our easy-to-access geospatial estimates of survey data quality highlight the need to invest in better targeting of household surveys in remote areas.